The weighted risk and relationship with patients: ambivalent aspect of medicine. - Bignamini, Angelo A. (Medicina e Morale, 2003)
The physicians and their patients are under pressure so that the risk of future diseases is regularly assessed, and measures are applied for their primary and secondary prevention. The paper focuses some problems originated from this policy, addressing the reliability of the algorithms and the difficulty to reach the recommended objectives. This paper discusses, based on real data from an observational study, some ethical concerns relevant to population screening, to the systematic implementation of preventive measures as recommended in the guidelines, and more generally to the "culture of prevention". The critical points discussed include the need to consider that the individual subject is not the average representative of the population, but an individual subject with unique characteristics, predicaments, and sensibility; the awareness that the prevention can be effective on the population but not necessarily in the individual subject; the consciousness that the objectives set to decrease the risk should actually be within real reach, involving the subject's autonomy-responsibility beyond the guidelines' recommendations; that reaching the objective does not necessarily mean a favourable outcome. The paper also point to the insistence on preventive measures as expressing the loss of the sense of the limit to the right to life and to the safeguard of health, that is, an expression of the refusal of the meaning of illness and death.<7p>